POLAKOMUNIKASIANTARAORANGTUADANANAKDALAM MENCEGAH TAWURAN REMAJA (Studi Kasus di Kawasan KelurahanTanahTinggi,KecamatanJoharBaru,JakartaPusat) - Rosacelia, Denis; Utama, Dedy Kusna; Ekasari, Retno (LUGAS Jurnal Komunikasi, 2024)
Communicationpatternscancreateabetterrelationshipandbuildclosenessbetweenparentsandchildreniftheprocessofcommunication patterns goes well. Lack of interpersonalcommunicationbetweenparentsandchildreninpreventingbrawlsbetweenteenagerswasfoundintheJoharBarusubdistrict,CentralJakarta.Lackofinteractionandsupervisionbyparentsandchildren,andlackofchildren'sethicsaresomeoftheproblemsinseveralfamilies,whicharesomeofthefactorscausingtheriseofbrawlsbetweenteenagersintheJoharBarusubdistrict,CentralJakarta.ThepurposeofthisstudywastoexaminethepatternofcommunicationbetweenparentsandchildreninpreventingjuvenilebrawlsintheJohar Barusubdistrict,CentralJakarta.The theoryusedinthis studyisthepatterncommunicationbyDeVito,namely,sendingandreceivingmessages,competence,messages,communication channels,noise,context,impact,andethics.Theresearchmethodusedisdescriptivequalitativeresearch,withinterviewandobservationmethodsasdatacollectiontechniques.Theresultsshowthatthepattern of communication betweenparentsandchildreninpreventingjuvenilebrawlsintheJoharBarusubdistrict,CentralJakartahasbeen going well in the aspect of messages, namely effectiveness in delivering messages, and media communication channels in communicating. While in the aspect of sending and receiving messages,theintensityoftheprocessofexchanginginformation,competence,namelyopennessincommunication,noisefromdisturbancesinthecommunicationprocess,theenvironmentalcontextinthecommunicationprocess,theimpactofeffectsthatoccurafterthecommunicationprocess,andethicalattitudesincommunicating,arestillnotwellestablishedsothathinderthecommunicationprocess.